2015
DOI: 10.1152/ajpregu.00464.2014
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated muscle metaboreflex-induced pressor response during postexercise muscle ischemia in renovascular hypertension

Abstract: DS. Attenuated muscle metaboreflex-induced pressor response during postexercise muscle ischemia in renovascular hypertension. Am J Physiol Regul Integr Comp Physiol 308: R650 -R658, 2015. First published January 28, 2015 doi:10.1152/ajpregu.00464.2014.-During dynamic exercise, muscle metaboreflex activation (MMA; induced via partial hindlimb ischemia) markedly increases mean arterial pressure (MAP), and MAP is sustained when the ischemia is maintained following the cessation of exercise (postexercise muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 65 publications
(107 reference statements)
1
16
0
Order By: Relevance
“…However, in heart failure (HF) this response appears to be abolished (Kaur et al, 2015b). In the study by Spranger et al (2015) the authors noted a hint of this shift in the mechanisms mediating the metaboreflex in the animals after induction of hypertension inasmuch as the small rise in peripheral vascular conductance during metaboreflex activation often noted in normal animals was abolished after induction of hypertension. This could indicate greater peripheral sympatho-activation during metaboreflex activation after induction of hypertension and/or reduced beta mediated vasodilation.…”
Section: Skeletal Muscle Afferentsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in heart failure (HF) this response appears to be abolished (Kaur et al, 2015b). In the study by Spranger et al (2015) the authors noted a hint of this shift in the mechanisms mediating the metaboreflex in the animals after induction of hypertension inasmuch as the small rise in peripheral vascular conductance during metaboreflex activation often noted in normal animals was abolished after induction of hypertension. This could indicate greater peripheral sympatho-activation during metaboreflex activation after induction of hypertension and/or reduced beta mediated vasodilation.…”
Section: Skeletal Muscle Afferentsmentioning
confidence: 98%
“…A study by Ranadive et al (2017) showed that there was no differences in muscle metaboreflex responses between women with a history of hypertensive pregnancies when compared to women that had normotensive pregnancies. Studies in conscious dogs concluded that metaboreflex-induced increases in MAP, cardiac output (CO), stroke volume (SV) and HR were reduced in dogs after induction of hypertension (Sala-Mercado et al, 2013) and that these attenuated responses were less sustained during PECO (Spranger et al, 2015). Previous studies in canines and humans have shown that when cardiac function is impaired the mechanisms mediating the metaboreflex pressor response during submaximal dynamic exercise “switch” from primarily increases in CO to primarily peripheral vasoconstriction (Hammond et al, 2000; Kim et al, 2005a; Crisafulli et al, 2011; Sala-Mercado et al, 2013).…”
Section: Skeletal Muscle Afferentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, neural signals from central command recruit motor units for muscle contraction and stimulate ACV regulation areas in the brainstem. The activation of sensitive skeletal muscle afferent neurons (metaboreflex and mechanoreflex) regulates the SMEPR that stimulates the brainstem areas 13 . Thus, sensory information to the central nervous system controls the efferent responses to the cardiovascular system.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, LIRE‐BFR induces an increase in sympathetic nerve activity and decrease in parasympathetic nerve activity which are modulated by the arterial baroreflex 14 . Thus, these autonomic responses increase heart rate, cardiac output, cardiac contractility, and blood pressure 13 . As a result, these hemodynamic changes promote an elevation in arterial resistance and reduction in venous capacitance 15 …”
Section: Introductionmentioning
confidence: 99%